Kwasi Wiredu’s Consensual Democracy And The Problem Of Identity Politics - Adjei-Mawutor, G. (University Of Ghana, 2022)
This thesis argues for a critical application of Wiredu’s consensual democracy to the problem of identity politics that have bedevilled postcolonial Africa. By doing so, it lays bare the present understanding of identity and identity politics and contextualises this to the African experience. The thesis, proceeding through an historico-philosophical examination of colonialism, surveys the tension between the imperial ideologies of legitimation and the anticolonial ideologies of legitimation, uncovering the deficiencies that resulted in the numerous catastrophes in the short existence of many African postcolonial nation-states. Subsequently, a case for a reconfiguration of the postcolonial African nation-state is made to divorce it from all colonial imperatives. The thesis also compares colonially inspired majoritarian democracy and indigenously inspired consensual democracy, emphasising the foundational presuppositions between these concepts as grounds for evaluation. I argue using the moderate communitarian framework that consensual democracy if applied through the primordial public allows for the hybridisation and nomadization of identities; thus, as conceived by Wiredu, political associations open the space for people to associate with different political associations that fits their perspectives. It is further argued that this reduces the dimension of antagonism among political associations (a dimension that affects political parties in majoritarian democracy) and instead transforms this dimension into agonism, thereby removing the tendency to politicise identities and thus diffusing the tendency to identity politics.
MPhil. Philosophy
Keywords: Democracy; Identity Politics; Kwasi Wiredu; Consensual